Nanometrology - Nanopositioning- and nanomeasuring machine with integrated nanoprobes - Jäger, Gerd; Hausotte, Tino; Manske, Eberhard; Büchner, Hans-Joachim; Mastylo, Rostyslav; Vorbringer-Dorozhovets, Nataliya; Füßl, Roland; Grünwald, Rainer (Trans Tech Publications, 2006)
The integration of several, optical and tactile probe systems and scanning force microscopes makes the NPM-Machine suitable for various tasks, such as large-area scanning probe microscopy, mask and water inspection, circuit testing as well as measuring optical and mechanical precision work pieces such as micro lens arrays, concave lenses, mm-step height standards.
Keywords: nanometrology; nanopositioning; nanoprobes; interferometers